2019
DOI: 10.3846/transport.2019.10402
|View full text |Cite
|
Sign up to set email alerts
|

Beacon Technology for Real-Time Informing the Traffic Network Users About the Environment

Abstract: Informing the users about their environment is of extreme importance for their full and independent functioning in the traffic system. Today’s development of technology provides the user the access to information about their environment by using the smartphone device at any moment if there is a defined applicative solution. For this, it is necessary to define the user’s environment according to the Ambient Assisted Living (AAL) concept, which understands adequate technology of gathering, processing and distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…For such person categories, engineering structures are developed and information tools are introduced based on smart technologies that increase the driving safety on street and road networks. Information to these persons about the current traffic functioning can be obtained through the corresponding applications in smartphones, as well as smart bracelets [40][41].…”
Section: A126mentioning
confidence: 99%
“…For such person categories, engineering structures are developed and information tools are introduced based on smart technologies that increase the driving safety on street and road networks. Information to these persons about the current traffic functioning can be obtained through the corresponding applications in smartphones, as well as smart bracelets [40][41].…”
Section: A126mentioning
confidence: 99%
“…Customizable thresholds are proposed to avoid undesirable triggers and save staff team resources in the occurrence of a false accident. Human actions can be automated according to the numeric data type presented in Table 2, and the results of their correlation presented in Equation (11).…”
Section: False-positive Avoidancementioning
confidence: 99%
“…It has been suggested that smartphone sensors associated with mobile applications produce powerful solutions, such as learning the behavior and trajectory issues of blind and partially sighted people. [7][8][9][10][11] These solutions consider the combined use of cloud computing with global navigation satellite system (GNSS), near field communication (NFC), bluetooth, wifi, radiofrequency identification (RFID), or global system for mobile (GSM) communication technologies.…”
mentioning
confidence: 99%
“…Second, it is difficult to design appropriate feature sets to detect vehicle violations of multientity interactions. For example, careful consideration of the movement of the blind and visually impaired persons in the traffic intersection is required, [20][21][22][23] to accurately identify the validity of pedestrian behavior. Finally, it is challenging to develop an appropriate optimization algorithm applicable to pedestrian violation datasets due to the weak supervision of relevant datasets.…”
Section: Introductionmentioning
confidence: 99%